Pengaruh Citra Instansi, Kompensasi, dan Motivasi Kerja Terhadap Loyalitas Pegawai Biro Keuangan pada Kementerian Agama RI Pusat - Hardyansyah , Muhammad; Dahlan , Rahmat (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research is entitled "The influence of agency image, compensation and motivation on employee loyalty at the Finance Bureau of the Ministry of Religion of the Republic of Indonesia" which aims to determine the partial or simultaneous influence of agency image, compensation and work motivation on employee loyalty. This research uses descriptive quantitative research with a population There are 30 employees in the Finance Bureau of the Central Republic of Indonesia's Ministry of Religion and the sample for this research is 30 respondents. The data collection methods used were literature studies, interviews and questionnaires and analyzed using regression, t test and f test with the help of the SPSS 26 application. The results of this study showed that image influence had a partial effect on employee loyalty of 1.910. employee loyalty is 2,783. Meanwhile, work motivation has a partial effect on employee loyalty of 2.364, and agency image, work motivation and work motivation have a simultaneous effect on employee loyalty of 3.629.